O coronelismo nas narrativas de Wilson Lins: espaços de poder - Galvão, André Luís Machado (2010)
The Colonels is a social phenomenon of great relevance in Brazil, especially in the Northeast, where they flourished and established itself with greater breadth and influence. Despite being the subject of important sociological studies, the subject has been little studied in the fictional field, which has rarely been studied, despite having been reported by authors in fiction canon of national literature, such as Jorge Amado and José Lins do Rego. In that sense, this paper examines the writer's trilogy of colonels Wilson Lins, composed of works Os Cabras do Coronel (1964), O Reduto (1965) and Remanso da Valentia (1967), from the perspective of power in its multiple characteristics and relationships, from the standpoint of sociological, historical, political and cultural. It analyzes the sociological conception of the phenomenon and its consequences in the works studied, the relations between the fictional and historical discourse, the tension and negotiation between authorities in the trilogy and the approach of female character, relating to the common patriarchal power Colonels of the formation of fictional character. From the proposed analysis, there is a broad overview of how the fictional context of the Colonels in the hinterland of Bahia identify with their national sociological perspective and how the trilogy in the study presents evidence for identifying the various Power relationships within that context.